2010
DOI: 10.2169/internalmedicine.49.3518
|View full text |Cite
|
Sign up to set email alerts
|

Chylous Ascites and Chylothorax: An Unusual Manifestation of Cardiac Amyloidosis

Abstract: Restrictive cardiomyophthy is an extremely rare cause of massive chylous ascites and chylothorax. We report a 56-year-old man patient who presented with chylous ascites and bilateral chylothorax; 12-lead electrocardiography and echocardiography revealed restrictive cardiomyopathy. Endomyocardial biopsy disclosed amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…These include right heart failure, dilated cardiomyopathy and constrictive pericarditis. Chen et al, reported a case of chylous ascites secondary to cardiac amyloidosis, where the contributing factor was thought to be increased left subclavian venous pressure. Both acute necrotizing pancreatitis and chronic pancreatitis are associated with chylous ascites; the underlying mechanism remains unknown but is thought to be due to direct compression of lymphatic channels …”
Section: Methodsmentioning
confidence: 99%
“…These include right heart failure, dilated cardiomyopathy and constrictive pericarditis. Chen et al, reported a case of chylous ascites secondary to cardiac amyloidosis, where the contributing factor was thought to be increased left subclavian venous pressure. Both acute necrotizing pancreatitis and chronic pancreatitis are associated with chylous ascites; the underlying mechanism remains unknown but is thought to be due to direct compression of lymphatic channels …”
Section: Methodsmentioning
confidence: 99%
“…Chylous ascites and chylothorax are rare, and the classic findings of orbital purpura and macroglossia are highly suspicious for AL amyloidosis. [4][5][6] The prevalence of cardiac amyloidosis is not known because it frequently goes undiagnosed. Wild-type TTR may be suspected but not biopsy proven since management prior to the introduction of novel agents had been supportive unless there was an underlying plasma cell disorder.…”
Section: Discussionmentioning
confidence: 99%
“…5 Chylous ascites and chylothorax are rare complications. 6 The mechanism is unclear, but it is believed that the elevated venous pressure secondary to heart failure results in left subclavian venous distension and stiffness that impairs lymphatic fluid return. Chylous fluid subsequently leaks into the pleural and peritoneal spaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other conditions that have been reported to be the cause of chylothorax and chylous ascites, include liver cirrhosis, hypothyroidism, nephrotic syndrome and abdominal operations [7]. Notwithstanding the above conditions, the coexistence of chylothorax and chylous ascites also can be caused by cardiac problems, such as ischemic cardiomyopathy, constrictive pericarditis and cardiac amyloidosis [8]. …”
Section: Discussionmentioning
confidence: 99%